BLACK COLORATION ON THE OLFACTORY SACS OF SCOLlODON CAUGHT OFF BOMBAY - Ghate, H V (Indian Journal of Fisheries, 2011)
The frozen sharks come to Pune from the Bombay market and are presumably caught off Bombay. Owing to long storage in ice. the detailed histological picture was difficult to obtain. Studies on freshly collected sharks are necessary to understand the basis of this pathological condition and to know whether it has any relation with water quality.